Enhancement of bio-methane production yield from rumen digesta with biodegradable kitchen wastes by co-digestion process - Rashed Al Mamun, Muhammad; Muhammed, Mahdi; Sultana Urme, Nadira; Janibul Alam Soeb, Md. (International Journal of Engineering and Technology, 2020)
The study was investigated to enhance biogas production from rumen digesta by anaerobic co-digestion process. The experiment was carried out in 3300 mL digester. The mixing ratio of rumen digesta and water used was 1:1 in 40 days Hydraulic Retention Time (HRT). Produced gas was measured by volumetric water replacement method. In phase-1, the maximum biogas generation from digesta of chicken and goat, cow and chicken, cow and goat, and co-digestion of four substrates (C:CH:G:V) were 65, 1230, 37 and 375 mL/d at 17th, 14th, 26th and 13th day respectively. The average biogas production was found from these samples were 20, 340, 16 and 113 mL. In phase-2, the maximum biogas generation from cow, goat and chicken, cow, chicken and vegetable waste and cow, goat and vegetable waste were respectively 66, 80 and 64 ml/d at 19th, 23rd and 27th day. The average biogas generation were found from these samples 22, 32 and 19 mL. The comparative data shows, biogas production is higher with cow and chicken wastes in both the phases mixed with vegetable waste. Thus, it is suggested that the study which gave maximum yield of biogas production from co-digestion process might be met the future energy demand.Â Â